A summer of horses - Fenner, Carol (New York : Knopf : Distributed by Random House, 1989)
Ten-year-old Faith struggles to overcome her fear of horses and her feelings of jealousy towards her talented, older sister when they spend the summer on a horse farm.
"Bullseye books."
Booklist
5.7
3-6
Keywords: Horses -- Fiction; Sisters -- Fiction; Fear -- Fiction; Horses -- Fiction; Sisters -- Fiction; Fear -- Fiction